A new species and a new variety of Meliolaceae fungi from India - Sabeena, Aliyarukunju; Biju, Haridas (Phytotaxa, 2022)
Two new foliicolous fungal taxa from Andaman Islands in the Bay of Bengal and Ponmudi forest areas of Kerala are described and illustrated. Meliola veebeehosagoudarii on Helicia excelsa is a new species while Asteridiella elaeocarpicola var. gadgilii on Elaeocarpus gadgili is described as a new variety. Both taxa are compared morphologically with similar taxa reported on members of Proteaceae and Elaeocarpaceae families, respectively.